Normal very long-chain fatty acids level in a patient with peroxisome biogenesis disorders: a case report - Bita Barazandeh Shirvan; Najmeh Ahangari; Razie Rezaie; Parvaneh Layegh; Ehsan Ghayoor Karimiani; Narges Hashemi; Mehran Beiraghi Toosi (BMC, 2024)
Abstract Background Zellweger spectrum disorders (ZSDs) are a group of peroxisome biogenesis disorders (PBDs) with different variants in the PEX genes. The main biochemical marker for screening peroxisomal disorders is very long-chain fatty acids (VLCFAs). The study reveals a rare case of PBD in the Zellweger spectrum in which she had normal plasma VLCFA levels. Case presentation Here, we report a 10-year-old girl with neurodevelopmental delay, facial dysmorphism, and hearing impairment. A brain magnetic resonance imaging scan was done to determine the reason for the seizures and neurodevelopmental delay. MRI images showed a mild widening in sulci especially in frontal lobes and sylvian fissures with pachygyria in the perisylvian regions. Biochemical analysis was done to detect ZSD. However, plasma VLCFA levels were normal. The diagnosis was made using whole-exome sequencing (WES). A homozygous variant of uncertain significance (VUS) in PEX6 NM_000287.4: c.1992G > C (p. Glu664Asp) was identified which has been confirmed through Sanger sequencing in probands and her parents. Conclusions According to the case report, plasma VLCFA levels can be normal in patients with PBDs in the Zellweger spectrum. Furthermore, we could re-classify the c.1992G > C variant in the PEX6 gene from VUS to likely pathogenic based on clinical manifestations including facial dysmorphism, and hearing impairment.